2021
DOI: 10.1111/jpy.13177
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genomics of a critically endangered brown seaweed

Abstract: Seaweeds provide valuable ecosystem services, but many are undergoing global decline due to climate and anthropogenic stressors. The brown macroalga, Nereia lophocladia (hereafter called Nereia), is among only a handful of seaweeds globally to be listed as critically endangered and is only described from two known locations, but there exists little knowledge about this species. Here, we combine field surveys to verify the distribution of Nereia, with cutting‐edge genomics to determine genetic diversity and pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This alga was shown to have low genetic diversity (H e = 0.055) and high inbreeding rate (F is = 0.721) within populations and high genetic differentiation among populations by using SNP markers. It was suggested that the low genetic diversity and high level of inbreeding render this species vulnerable to predicted ocean change (Mamo et al, 2021). By comparison, we revealed high genetic diversity in the Chinese native populations of U. pinnatifida based on mitochondrial and nuclear markers.…”
Section: Populationmentioning
confidence: 70%
See 1 more Smart Citation
“…This alga was shown to have low genetic diversity (H e = 0.055) and high inbreeding rate (F is = 0.721) within populations and high genetic differentiation among populations by using SNP markers. It was suggested that the low genetic diversity and high level of inbreeding render this species vulnerable to predicted ocean change (Mamo et al, 2021). By comparison, we revealed high genetic diversity in the Chinese native populations of U. pinnatifida based on mitochondrial and nuclear markers.…”
Section: Populationmentioning
confidence: 70%
“…Fitness of such populations are more likely to be impaired by inbreeding depression, making them more vulnerable to anthropogenic stressors. The endangered brown macroalga Nereia lophocladia in Australia is an example of such populations (Mamo et al, 2021). This alga was shown to have low genetic diversity (H e = 0.055) and high inbreeding rate (F is = 0.721) within populations and high genetic differentiation among populations by using SNP markers.…”
Section: Populationmentioning
confidence: 99%
“…The genetic diversity of a population shows a positive correlation with its adaptive potential and fitness, and extreme loss of genetic diversity (genetic erosion) can lead to and be a consequence of inbreeding, a decline in fitness, and an increased risk of extinction [ 11 ]. Knowledge of genetic erosion can contribute and motivate the assessment of the conservation status of threatened or endangered species, e.g., for classification under the IUCN Red List framework, as well as for developing management responses ( Table 1 and Fig 1 (action 1)) [ 12 ] (but see [ 13 ] on a cautionary note of using genetic diversity information at neutral loci only). Neutral loci are useful for estimating gene flow among populations (i.e., connectivity), introgression between species, and effective population sizes.…”
Section: Genetic and Genomic Diversity Data To Inform Marine Conserva...mentioning
confidence: 99%
“…Genomic tools can complement the information generated by field and mesocosm experiments providing a mechanistic understanding of the genetic basis of local adaptation. Progressive reduction of costs of next-generation sequencing techniques has fostered the production of genomic information and is giving momentum to conservation genomics of marine forests (Mamo et al, 2021). For instance, Wood et al (2021) characterized neutral and adaptive genetic diversity in the brown seaweed Phyllospora comosa and how it correlates with temperature, generating an insight into genetic vulnerability under warming climates, crucial information for climate-proof restoration of this species.…”
Section: Next Challenges and Perspectives In Ecological Researchmentioning
confidence: 99%